Micro-magnetic resonance imaging of avian embryos - Li, Xiaojing (Blackwell Science Inc, 2007)
Chick embryos are useful models for probing developmental mechanisms including those involved in organogenesis. In addition to classic embryological manipulations, it is possible to test the function of molecules and genes while the embryo remains within the egg. Here we define conditions for imaging chick embryo anatomy and for visualising living quail embryos. We focus on the developing limb and describe how different tissues can be imaged using micro-magnetic resonance imaging and this information then synthesised, using a three-dimensional visualisation package, into detailed anatomy. We illustrate the potential for micro-magnetic resonance imaging to analyse phenotypic changes following chick limb manipulation. The work with the living quail embryos lays the foundations for using micro-magnetic resonance imaging as an experimental tool to follow the consequences of such manipulations over time.